Exosomes isolation and characterization in serum is feasible in non-small cell lung cancer patients: critical analysis of evidence and potential role in clinical practice - Taverna, S. (2016)
Exosomes are nano-sized vesicles of endolysosomal origin, released by several cytotypes in physiological and pathological conditions. Tumor derived exosomes, interacting with other cells of the tumor microenvironment, modulate tumor progression, angiogenic switch, metastasis, and immune escape. Recently, extracellular vesicles were proposed as excellent biomarkers for disease monitoring and prognosis in cancer patients. Non-small cell lung cancer (NSCLC) has a poor 5-year survival rate due to the delay in the detection of the disease. The majority of patients are diagnosed in an advanced disease stage. Exosomes might be promising beneficial tools as biomarker candidates in the scenario of NSCLC, since they contain both, proteins and miRNAs. The clinical case reported in this manuscript is a proof of concept revealing that NSCLC exosomes and sorted miRNAs might constitute, in a near future, novel biomarkers. This review summarizes the role of exosomes in NSCLC, focusing on the importance of exosomal microRNAs in lung cancer diagnosis and prognosis.